2017
DOI: 10.1021/jacs.7b03159
|View full text |Cite|
|
Sign up to set email alerts
|

The Suzuki–Miyaura Coupling of Nitroarenes

Abstract: Synthesis of biaryls via the Suzuki-Miyaura coupling (SMC) reaction using nitroarenes as an electrophilic coupling partners is described. Mechanistic studies have revealed that the catalytic cycle of this reaction is initiated by the cleavage of the aryl-nitro (Ar-NO) bond by palladium, which represents an unprecedented elemental reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
107
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(116 citation statements)
references
References 34 publications
5
107
0
2
Order By: Relevance
“…Widdowson and Wilhelm reported that the nitro group in the ortho position to the halo atom of the haloarene 5 (Scheme ) is not only acting as an electron withdrawing group, but also as a coordinating group for incoming palladium in the Suzuki cross‐coupling and thereby act a significant influence on the C–C coupling. This was recently supported by a study disclosed by Sakaki, Nakao, and collaborators, which revealed that the NO 2 group of nitroarenes even operated as the leaving group in the Suzuki cross‐coupling. These observations explain the difficulties of using ortho‐ NO 2 substituted reagents in the Suzuki cross‐coupling experiments.…”
Section: Figurementioning
confidence: 99%
“…Widdowson and Wilhelm reported that the nitro group in the ortho position to the halo atom of the haloarene 5 (Scheme ) is not only acting as an electron withdrawing group, but also as a coordinating group for incoming palladium in the Suzuki cross‐coupling and thereby act a significant influence on the C–C coupling. This was recently supported by a study disclosed by Sakaki, Nakao, and collaborators, which revealed that the NO 2 group of nitroarenes even operated as the leaving group in the Suzuki cross‐coupling. These observations explain the difficulties of using ortho‐ NO 2 substituted reagents in the Suzuki cross‐coupling experiments.…”
Section: Figurementioning
confidence: 99%
“…Studies in Suzuki cross‐coupling reactions have mainly focused on the development of new ligands and catalysts and no new work except that of Nakao et al has been done in this area. There is therefore a need for an innovative and general procedure for direct Suzuki coupling of phenols that is devoid of the above‐mentioned problems.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ligands examined for aminations by Buchwald and co-workers, BrettPhos [14] (L1)w as the most effective to afford 4-methyl-N,N-diphenylaniline (3aa)i n5 5% yield (entry 1). As ubsequent investigation of bases (entries [10][11][12][13][14] revealed that the use of predried K 3 PO 4 increased the yield of 3aa to 75 %( entry 10), whereas K 2 CO 3 and Cs 2 CO 3 resulted in poorer yields (entries 11 and 12). Other phosphine ligands conventionally employed in Buchwald-Hartwig amination such as DPPF,B INAP,a nd P(t-Bu) 3 did not generate 3aa (entries 7-9).…”
mentioning
confidence: 99%
“…As previously demonstrated, nitroarenes react with palladium(0) complex A to form h 2 -arene palladium(0) complexes such as B.T his step is followed by oxidative addition of the CÀNO 2 bond to afford C.Subsequently,anamine nucleophile can react with C in the presence of abase to afford arylpalladium amide D,which can undergo reductive elimination to generate arylamine 3 and arene ligand exchange to regenerate A.W hent he oxidative addition adduct 4,w hich was prepared according to our previous report, [12] was reacted with 2f at 50 8 8Ci nt he presence of K 3 PO 4 ·n H 2 O, N-benzylaniline was obtained in 53 %y ield [Eq. As previously demonstrated, nitroarenes react with palladium(0) complex A to form h 2 -arene palladium(0) complexes such as B.T his step is followed by oxidative addition of the CÀNO 2 bond to afford C.Subsequently,anamine nucleophile can react with C in the presence of abase to afford arylpalladium amide D,which can undergo reductive elimination to generate arylamine 3 and arene ligand exchange to regenerate A.W hent he oxidative addition adduct 4,w hich was prepared according to our previous report, [12] was reacted with 2f at 50 8 8Ci nt he presence of K 3 PO 4 ·n H 2 O, N-benzylaniline was obtained in 53 %y ield [Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation